Cellular immune responses to recombinant heat shock protein 70 from Histoplasma capsulatum. - Allendoerfer, R (1996)
Heat shock protein (hsp) 70 from several microbes is antigenic in mammals. In this study we sequenced and expressed the gene encoding this protein from Histoplasma capsulatum to study its immunological activity. The deduced amino acid sequence of the gene demonstrated 71 and 76% identity to hsp7O from humans and Saccharomyces cerevisiae, respectively. A cDNA was synthesized by reverse transcription-PCR and was expressed in Escherichia coli. Recombinant protein reacted with a mouse monoclonal antibody raised against human hsp7O. Splenocytes from C57BL/6 mice immunized with recombinant hsp7O emulsified in adjuvant, but not yeast cells, reacted in vitro to the antigen. Recombinant hsp7O elicited a cutaneous delayed-type hypersensitivity response in mice immunized with protein or with viable yeast cells. Mice were injected with recombinant hsp7O and challenged intranasally with a sublethal inoculum of yeast cells. Vaccination did not confer protection in this model. Thus, recombinant hsp7O can induce a cell-mediated immune response but does not induce a protective response.